Molecular characterization and pathogenicity study of a highly pathogenic strain of chicken anemia virus that emerged in China - Fang, Lichun; Jia, Huiyue; Hu, Yuhang; Wang, Yixin; Cui, Zhizhong; Qi, Lihong; Zhao, Peng (Frontiers in Cellular and Infection Microbiology, 2023)
Chicken infectious anemia (CIA) is caused by chicken anemia virus (CAV). Recently, severe anemia have emerged in layer chickens (8 to 10-week-old) on poultry farms in China. However, the etiological characteristics and pathogenic potential of CAV in chickens at 6 weeks or older are not well understood. In this study, we isolated a CAV strain, termed SD15, from 2-month-old chicken with severe anemia and analysed the genetic evolution relationship. We found that strain SD15 had the highest homology (98.9 %) with CAV18 strain. Comparison with 33 reference strains revealed 16 amino acid mutations in strain SD15, 2 of which were previously unknown (F210S in VP1 and L25S in Vp3). Compared with low pathogenic strains (Cux-1 and C14), highly pathogenic strains (SDLY08 and SD15) had 3 base mutations in their noncoding region. To further understand its pathogenicity, 10-week-old specific-pathogen-free (SPF) chickens were challenged with the novel strain and SDLY08. No obvious clinical symptoms were observed in the SDLY08 group. However, SD15-infected chickens showed significant growth retardation and immunosuppression. The main manifestations of immunosuppression were the significantly reduced thymus and bursa indices and AIV-H9 vaccine-induced antibody levels (P < 0.05). The lowest number of red blood cells in the SD15 group was just 60 % of that in the control group. Taken together, the novel strain SD15 not only showed higher pathogenicity but also exhibited the potential ability to break the age resistance of older chicken to CAV. Our study enhanced the understanding of the epidemiological characteristics of chicken infected with severe anemia and can facilitate the development of improved control strategies of CIA in China.